Social movements, globalization, and the reconfiguration of Mexican/Chicano nationalism - McCaughan, Ed (Social justice, 1999)
Part of a special issue on collective identities, social problems, and movements. The writer discusses the reconfiguration of Mexican/Chicano nationalism in relation to social movements and globalization. He traces the history of Mexican nationalism from the Mexican revolution through to the Chicano movement in the U.S. He outlines the different ongoing efforts on both sides of the border to reconfigure collective identities and programs for social change that challenge the limits of the old nationalist program. He describes how progressive, movement-associated actors are combining ancient, pre-national claims of injustice with an awareness of 20th-century social movements and are ridding themselves of racism, sexism, and parochialism.